Sources of Psychological Stress among Students of Sports Sciences at Mu’tah University - Almaaitah, Mona (Dirasat: Educational Sciences, 2022)
Objectives: The study aims to identify the sources of psychological stress among students of School of Sports Sciences at Mutah University, according to the variables of gender and academic year. The study sample was chosen by a stratified method, and its number was (87) out of (550) students registered in the second semester of the academic year 2018/2019. The proportion of the sample from the community was (15%). Methodology: To achieve the goal of the study, a descriptive approach was used. A questionnaire was built from five areas: social, academic, economic, health, and personal, distributed over (37) items. Results: The results showed that psychological stress among students of School of Sports Sciences at Mutah University was high in the social, academic, and economic fields, and low in the health and personal fields. The results also showed the absence of statistically significant differences in psychological stress due to the gender variable, and the presence of statistically significant differences due to the variable of the academic year. Conclusions: The study recommends setting a credit hour for social and psychological counseling for students of the School of Sports Sciences at Mutah University in their first year to prepare them psychologically to deal with theoretical and practical lectures in the field of physical education.